PROMOTING HEALTH EDUCATION- CHANGING LIFESTYLES - Asmawi, Qurratul (Universiti Teknologi PETRONAS, 2011)
According to Health Facts published by Ministry of Health Malaysia (MOH) in 2010 most non communicable disease (NCD) consists of diseases that are implications of unhealthy lifestle are the main causes of death in Malaysia. This translates into the need of educating citizens on how to have a healthy lifestyle to avoid the risks of getting fatal NCDs. A Heahh Education Division has already been set up as one of the 5 division under the Public Health Department Ministry of Heahh Malaysia that could be seen through their various websites. The issue is the lack effectiveness of the website to educate regardless of the increasing number of online users. Thus, this research is planned to effectively conduct health education to reach the online citizens by the use of Human Computer Interaction theories as well as a learning theories. The main objective ofthis project is to implement these two theories in the development of the website is to create awareness to the community on the importance of living a healthy life as well as the implications of doing otherwise. The content of the website includes the main criteria of lifestyle such as hygiene, nutrition and physical activities and the knowledge of how to conduct a healthy lifestyle base on the criteria, and the implications of not doing so. The website also displays basic information regarding the disease which includes the causes of the disease, the implications to the body, the implication towards the life of a patient infected with the disease, and what can be done to prevent the disease, as well as what can be done to help people infected with the disease. The educating and learning process is also equipped with risk assessments of diseases that would act as a decision support system to the users. The result of this project is the increase of interest and awareness regarding the importance and knowledge of having a healthy lifestyle among the internet users. The conclusion of this research project is conducting health education online is effective if the right theories and techniques are applied, as well as taking into account the user's perspective.